A Literary studies on social intelligence in technical education (Journal of Advances and Scholarly Researches in Allied Education, 2024)
In the rapidly evolving landscape of technical education, the integration of social intelligence skills has become increasingly significant. This study explores the role of social intelligence in technical education, emphasizing its impact on student performance, collaboration, and career readiness. Through a comprehensive literature review and qualitative analysis, we examine the various dimensions of social intelligence, including empathy, communication skills, adaptability, and conflict resolution, and their relevance to technical disciplines. Our findings indicate that social intelligence not only enhances the learning environment but also prepares students for the multifaceted challenges of the modern workplace. The study concludes by highlighting the necessity of incorporating social intelligence training in technical curricula and suggests practical strategies for educators to foster these skills in students.